(untitled) (Bioscience Journal, 2022)
Gaharu leaf extract produces yield extraction, phenol compound, and antibacterial activity in diverse quantities. The purpose of this research was to investigate the influence of the extraction method and type of solvent on the extractability of the polyphenol component and the antibacterial activity of gaharu leaves. Extraction was done through maceration and Soxhlet methods by using solvents of hexane, ethyl acetate, and ethanol. The extraction result showed that the highest yield value of 18.4% was found on the treatment of a combination of ethanol solvent and Soxhlet method. The total content of phenol and tannin of gaharu leaf extract was in the range of 11.2 to 18.62mg. mL-1 and 12.82 to 13.41%, respectively. Antibacterial activity of gaharu leaf extract on the Gram-positive test of Staphylococcus aureus was higher than that of the Gram-negative test of Escherichia coli having a value of zone of inhibition in the range of 5.33 to 6.33 mm and 4.00 to 5.00 mm, respectively.